Living with the Unknown: A Qualitative Study of Parental Experience of Prognostic Uncertainty in the Neonatal Intensive Care Unit - Krick, Jeanne A.; Weiss, Elliott Mark; Snyder, Anna; Haldar, Shefali; Campelia, Georgina D.; Opel, Douglas J. (American Journal of Perinatology, 2020)
Objective This study aims to characterize the experience of prognostic uncertainty for neonatal intensive care unit (NICU) parents.Study Design We conducted a qualitative interview study of current and former NICU parents regarding their experience with prognostic uncertainty in the NICU. Interviews were transcribed and analyzed using a grounded theory methodology.Results Twenty-four parents were interviewed before achieving thematic saturation. Three phases of the parental experience of prognostic uncertainty emerged: shock, gray daze, and looking forward. These phases often, but not always, occurred sequentially. In shock, parents felt overwhelmed by uncertainty and were unable to visualize a future for their family. In gray daze, parents felt frustrated by the continued uncertainty. While accepting the possibility of a future for their family, they could not conceptualize a path by which to achieve it. In looking forward, parents accepted uncertainty as inevitable and incorporated it into their vision of the future.Conclusion While each parent experienced the prognostic uncertainty in the neonatal intensive care unit in their own way, we found three common experiential phases. By understanding how a parent experiences prognostic uncertainty in these phases, providers may become better able to communicate and form therapeutic relationships with parents.
Keywords: neonatal intensive care unit; uncertainty; parent; communication